A review of π-conjugated polymer-based nanocomposites for metal-ion batteries and supercapacitors. Issue 10 (20th October 2021) - Uke, Santosh J.; Mardikar, Satish P.; Kumar, Ashwani; Kumar, Yogesh; Gupta, Meenal; Kumar, Yogesh
Abstract : Owing to their extraordinary properties of π-conjugated polymers (π-CPs), such as light weight, structural versatility, ease of synthesis and environmentally friendly nature, they have attracted considerable attention as electrode material for metal-ion batteries (MIBs) and supercapacitors (SCPs). Recently, researchers have focused on developing nanostructured π-CPs and their composites with metal oxides and carbon-based materials to enhance the energy density and capacitive performance of MIBs and SCPs. Also, the researchers recently demonstrated various novel strategies to combine high electrical conductivity and high redox activity of different π-CPs. To reflect this fact, the present review investigates the current advancements in the synthesis of nanostructured π-CPs and their composites. Further, this review explores the recent development in different methods for the fabrication and design of π-CPs electrodes for MIBs and SCPs. In review, finally, the future prospects and challenges of π-CPs as an electrode materials for strategies for MIBs and SCPs are also presented.